Potassium fertilisation with humic acid coated KCl in a sandy clay loam tropical soil - Rosolem, Ciro A. [UNESP]; Almeida, Danilo S. [UNESP]; Rocha, Kassiano F. [UNESP]; Bacco, Gustavo H. M. [UNESP] (Csiro Publishing, 2018)
Loss of potassium (K) by leaching after potassium chloride (KCl) application is common in light-textured, low cation exchangeable capacity (CEC) soils with predominance of 1 : 1 clay minerals, and is aggravated as soil K concentration increases. Coating of KCl with humic acids may be a strategy to avoid loss and supply K over the plant cycle. The objective of this study was to evaluate the response of maize (Zea mays) and soybean (Glycine max) to regular KCI and KCl coated with humic acid, as well as K leaching as affected by application of these fertilisers in single or split application to soils with different K levels. Field experiments with maize and soybean were conducted on soil with very low, low, and medium exchangeable K levels, in Botucatu, Brazil. Soybean and maize grain yields were higher with a single application of coated KCl compared with regular KCl, in soil with very low K level; however, when the rate was split, yields were higher with regular KCl. This shows the importance of fertiliser K release synchronisation as the plant develops, avoiding possible K losses by leaching in low CEC soils. Potassium leaching was observed in soil with medium K level. Potassium chloride coated with humic acids is an adequate source of K in low CEC soils with very low K level when applied in a single application at planting, as opposed to regular KCl that must be split. However, the coated fertiliser is not effective for avoiding K leaching in soils that arc medium or high in K.
Keywords: leonardite; maize; no-till; potassium leaching; slow release fertiliser; soybean